Research Note: A mixture of Bacteroides spp. and other probiotic intestinal anaerobes reduces colonization by pathogenic E. coli strain O78:H4-ST117 in newly hatched chickens - Papouskova, Aneta; Rychlik, Ivan; Harustiakova, Danka; Cizek, Alois (Poultry science, 2023)
An experimental group of one-day-old chicken from a commercial hatchery was given a defined mixture of 7 gut anaerobes. The next day the chicks were inoculated by an APEC strain O78:H4-ST117 resistant to ciprofloxacin, alongside with the control group and monitored for 4 wk after the inoculation for the presence of the colonizing strains and ciprofloxacin-resistant E. coli. Significant reduction of colonization rates in the first 2 wk was recorded in the experimental group for the numbers of ciprofloxacin-resistant E. coli. The results show that colonization of chicken by defined anaerobic mixtures may provide a decisive protection during the critical period of the chicken intestinal microflora development.
Keywords: kur domácí; Bacteroides; Animals; Probiotics; Escherichia coli Infections; infekce vyvolané Escherichia coli; avian pathogenic Escherichia coli (APEC); Escherichia coli; Chickens; chicken; Poultry Diseases; nemoci drůbeže; colonization; ciprofloxacin; Ciprofloxacin; probiotika; competitive exclusion; zvířata; probiotics